Growth performance and intestinal villous morphology alteration in pre-weaning piglets fed spray-dried porcine plasma in creep feed - Yamsakul,P. (Kasetsart University, 2015)
The effects of creep feed which included spray-dried porcine plasma (SDPP) were investigated on the growth performance and alteration of the intestinal villous morphology in seven-day-old piglets. The piglets were fed 0, 2, 4, and 6% SDPP diets for 24 d. The feed intake and body weight gain were measured during the experimental period. At the end of the experiment, the intestinal villus height, epithelial cell area and number of occurrences of cell mitosis were examined using light microscopy (LM), and the duodenal villus tip surface was observed using scanning electron microscopy (SEM). The results showed there was improved feed efficiency in the SDPP-fed group when compared with the control group. The 4% SDPP-fed group showed the highest improvement, followed by the 6% and 2% SDPP-fed groups, for most of the LM parameters in most intestinal parts. In addition, on the duodenal villus tip surface, the 0, 2, and 4% SDPP-fed groups showed a clearer cell outline, larger cells and protuberation of cells further into the lumen than those of the 6% SDPP-fed group. Thus, the results of this study showed that: the SDPP-fed group achieved improved feed efficiency after the feeding of dietary SDPP; the SDPP could be incorporated into piglet diets up to a level of 4%; and the SDPP might activate the intestinal function at both the villus and cellular levels.